Throwing cardiac rehabilitation into the 21st Century: a focus group study exploring the impact of COVID-19 on cardiac rehabilitation delivery in Victoria, Australia. (29th July 2021) - Cartledge, S; Rawstorn, J; Tran, M; Ryan, P; Howden, E; Jackson, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac rehabilitation (CR) education and exercise are predominantly delivered in group face-to-face settings. This delivery model was challenged during the COVID-19 pandemic due to government enforced lockdowns which restricted the delivery of these models of care. The Australian state of Victoria experienced the longest and most severe local restrictions and was in lockdown for approximately 26 weeks of 2020. Purpose: We aimed to explore the experience, barriers and enablers of delivering CR during a pandemic, and identify strategies for future COVID-safe programs among cardiac rehabilitation clinicians. Methods: Victorian members of the Australian Cardiovascular Health and Rehabilitation Association (ACRA) were invited to attend an exploratory qualitative online focus group in November 2020. An inductive thematic analysis was undertaken before deductively applying the Non-adoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) framework to identify barriers and enablers for technology adoption in CR. Results: 30 members participated in a 106 minute focus group. 17 members who provided demographics represented multiple disciplines (nursing n = 13, exercise physiology n = 3, physiotherapy n = 1) and geographical settings (metropolitan n = 10, regional n = 4, rural n = 3). Four main themes were identified: Consequences of sudden service delivery change; Technology use – challenges and benefits; Capacity (program and staff); and The way forward. The deductive NASSS analysis demonstrated the main challenges of continuing remotely delivered CR lie with all adopters (staff, patients, carers) and with organisations. Future CR strategies included the importance of resuming face-to-face programs but important barriers including finding capacity, particularly staffing, to run concurrent telehealth programs remain to be addressed. Conclusion: The COVID-19 pandemic forced and expedited significant changes to CR delivery models. While clinicians agreed that delivery of CR via telehealth will continue, it is now timely to review remote models of care and plan how they will integrate alongside traditional face-to-face programs.